Histo-morphological Study on the Sebaceous Glands of Prenatal Goat (Capra hircus) - Kumar, Prabhakar (Indian Journal of Veterinary Anatomy, 2019)
Thirty six goat foetuses were used to record the sequential histological changes that take places during the development of sebaceous gland in the skin of prenatal goat. The material was divided into three groups. The primordia of sebaceous glands were bud like and originated from the peripheral part of ordinary hair follicles and from the outer root sheath of sinus hair follicles at 102 days gestation in chin and face regions. These glands were noticed in all body regions from 114 days onwards. The sebaceous gland became alveolar in chin and face region at 114 days of gestation and in all body region from 118 days of gestation. Few glands originated directlyfrom epidermis at 108 and 145 days gestation in back and thigh regions, respectively.